Roles of CD4+ T cells as mediators of antitumor immunity - Kravtsov, Dmitriy S.; Erbe, Amy K.; Sondel, Paul M.; Rakhmilevich, Alexander L. (Frontiers in Immunology, 2022)
It has been well established that CD8+ T cells serve as effector cells of adaptive immune response against tumors, whereas CD4+ T cells either help or suppress generation of CD8+ cytotoxic T cells. However, in several experimental models as well as in cancer patients it has been shown that CD4+ T cells can also mediate antitumor immunity either directly by killing tumor cells or indirectly by activating innate immune cells or by reducing tumor angiogenesis. In this review, we discuss the growing evidence of this underappreciated role of CD4+ T cells as mediators of antitumor immunity.